Personnel policy adjustments when apprentice positions are unfilled: Evidence from German establishment data - Tina Hinz (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2016)
German firms have increasing difficulties in filling apprentice positions. I study how firms adjust their personnel policies when they face unfilled apprentice positions. Using the IAB Establishment Panel (2008-2014) and applying fixed effects panel estimations, I find that small firms react by hiring more unskilled workers. I do not observe an intensified use of personnel policies directed at the existing workforce, such as further training, retention of apprenticeship graduates or conversion of fixed-term into permanent contracts. Moreover, the results do not indicate that firms with unfilled apprentice positions turn away from apprenticeship training. My findings suggest that most training firms may not regard unfilled apprentice positions as a serious problem (so far). – – Deutsche Betriebe haben immer größere Schwierigkeiten ihre Ausbildungsstellen zu besetzen. Dieses Papier untersucht, wie Betriebe ihre personalpolitischen Maßnahmen anpassen, wenn Ausbildungsstellen unbesetzt bleiben. Unter Verwendung des IAB-Betriebspanels (2008-2014) und Schätzung mit betriebsfixen Effekten zeigt sich, dass kleine Firmen mehr geringqualifizierte Beschäftigte einstellen. Betriebe reagieren nicht mit einer intensiveren Nutzung von Maßnahmen der betrieblichen Weiterbildung, Übernahme von Auszubildenden oder Entfristung von Beschäftigten. Zusätzlich gibt es kein Anzeichen dafür, dass Betriebe mit unbesetzten Ausbildungsstellen ihre Ausbildungsaktivität verringern. Somit deuten die Ergebnisse darauf hin, dass Ausbildungsbetriebe mit unbesetzten Ausbildungsstellen (noch) keinen Handlungsbedarf sehen.
Keywords: I29; J24; J63; M53; 330; apprenticeship training; personnel policy; Germany